The Impact of Total Quality Management on the Organizational Performance - Sidney Mugenyi (Uganda Christian University, 2023)
This research studied the impact of total quality management on organizational performance: a case study of Coca Cola Beverage Uganda in Mukono district. The objectives of the study included: To assess the effect of process control on efficiency at CBC. To examine the impact of product design on sales at CBC. To determine how supplier quality management affects quality at CBC. Data was collected using self-administered questionnaires. The study used stratified and purposive sampling techniques to draw representative samples and 120 respondents were involved in the study. The findings showed that there were more men compared to women, most of the employees were more experienced at their work and aging that is to say above 18. The organization had more literate employees than the illiterate ones and most of employees were married. The researcher also found out the effect of process control on efficiency which include, reducing variability, increasing efficiency and ensuring quality. The findings of this study also revealed the impact of product designs on sales such as shaping the products quality, profitability, high costs, and customer satisfaction. The other findings also included the effect of supplier quality management on quality which included supplier development, competitive supplier selection, and supplier integration, measuring and monitoring performance of the supplier among others at Century Bottling Company. The researcher recommended Century Bottling Company to be efficient plants must quickly and effectively produce product with little waste, product design is labor intensive process which requires the contribution of highly trained specialists, and companies should master the best practices in supplier quality management at Century Bottling Company. Primary data for this research was collected using a well-designed and structured questionnaire which was made up of both close ended and open-ended questions. The key findings showed that CBC is practicing TQM but it is yet to implement it to the highest level of subscribing to a quality award system. The implementation of TQM is at the quality assurance level. It was found out that management inactions undermined leadership commitment, customer satisfaction, and TQM practices ineffective. It was concluded that there was the need to procure modern equipment to boost production. Again, the firm needs to diversify key portfolio in order to spread the overhead cost. Management must work to build trust amongst staff to improve on team work. It is also recommended that the company subscribe to a quality award system. For instance, ISO certification can help CBC practice TQM to the highest level to ensure customer confidence in the company's products.
This is a dissertation.